2012
DOI: 10.1039/c2cc36995h
|View full text |Cite
|
Sign up to set email alerts
|

Merging visible-light photoredox and Lewis acid catalysis for the functionalization and arylation of glycine derivatives and peptides

Abstract: A relay catalysis protocol for the functionalization of α-amino acids and dipeptides using a combination of visible-light photoredox and Lewis acid catalysis has been developed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
56
0
6

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 203 publications
(62 citation statements)
references
References 39 publications
0
56
0
6
Order By: Relevance
“…148 In this regard, catalytic protocols which utilize Lewis acids to enhance the rate of radical trapping have been reported. 149 Of particular note is a report by Yoon and co-workers demonstrating that conjugate additions of α-amino radicals can be rendered asymmetric through the use of a chiral i -BuPyBox-ligated Lewis acid catalyst (Scheme 31a).…”
Section: Photoredox Lewis Acid Catalysismentioning
confidence: 99%
“…148 In this regard, catalytic protocols which utilize Lewis acids to enhance the rate of radical trapping have been reported. 149 Of particular note is a report by Yoon and co-workers demonstrating that conjugate additions of α-amino radicals can be rendered asymmetric through the use of a chiral i -BuPyBox-ligated Lewis acid catalyst (Scheme 31a).…”
Section: Photoredox Lewis Acid Catalysismentioning
confidence: 99%
“…However, efforts towards expanding the scope of amines have been recently reported. Li [82] and Rueping [83] independently reported that N -arylglycine derivatives 65 are viable substrates (Scheme 16). They are presumably converted to imines 65a that are intercepted by indoles to give the Mannich-like adducts 67 .…”
Section: Reviewmentioning
confidence: 99%
“…5 In their work indoles in position C2 were successfully coupled with alkyl 2-(arylamino)acetates in the presence of Lewis acidic Zn(OAc) 2 and 1 mol% [Ir(ppy) 2 bpy]PF 6 photocatalyst.…”
Section: Lewis Acid Supported Photocatalysismentioning
confidence: 99%